Why is productivity so dispersed? - Griffith, Rachel; Haskel, Jonathan; Neely, Andrew (Oxford University Press, 2006)
Many papers have documented wide variations in productivity even in narrowly defined industries. Some have argued that this primarily reflects measurement problems due, for example, to comparing across different products. Others argue that this reflects persistent differences in performance due, for example, to management. This paper looks at productivity differences not within an industry but within a firm. We use data on productivity of different branches within lines of business of a major UK-based wholesaler. Using these productivity data for comparisons is, we argue, more likely to compare like with like than comparing between firms. We document sustained differences in productivity even between branches within the same line of business. We also discuss the extent to which they are correlated with differences in management and find that such differences ‘account’ for around 40 per cent of the difference in productivity.